Procesy adaptacyjne w języku polskich migrantów w Wielkiej Brytanii - Błasiak-Tytuła, Marzena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The author writes about the adaptation processes that occur in the language of Polish migrants who immigrated to the United Kingdom after 2004. One of the features of bilingual speech of Poles living and working in Britain are borrowings. Polish migrants willingly and spontaneously absorb the words and adapt them to the dialect of the Polish community. The borrowings become lexemes of the Polish community abroad as a result of the process of adaptation at different levels of the structure of language. The author discusses the graphical and morphological (inflectional and derivational) adaptation on the example of several dozen lexemes of the Polish community.